The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00441-009-0869-8
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarization-activated cyclic-nucleotide gated 4 (HCN4) protein is expressed in a subset of rat dorsal root and trigeminal ganglion neurons

Abstract: Hyperpolarization-activated cyclic nucleotide-gated (HCN) cation channels are active at resting membrane potential and thus are likely to contribute to neuronal excitability. Four HCN channel subunits (HCN1-4) have previously been cloned. The aim of the current study was to investigate the immunoreactivity of HCN4 channel protein in rat trigeminal (TG) and dorsal root ganglion (DRG) sensory neurons. HCN4 was present in 9% of TG neurons and 4.7% of DRG neurons, it was distributed in a discrete population of sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
1
21
0
2
Order By: Relevance
“…Chaplan et al (2003) also found HCN2 to be expressed by all sizes of DRG neurons in the rat, whereas in the mouse, HCN2 was expressed in about 80% and 60% of large-sized and small-sized DRG neurons, respectively (Moosmang et al, 2001). In the rat trigeminal ganglia, HCN2 has been shown to be expressed by all three neuronal size groups (Wells et al, 2007) or mainly by medium-large-sized neurons (Cho et al, 2009b). At least some of the IB4-negative small neurons that express HCN2 are likely to be lowthreshold mechanoreceptors because this subpopulation of primary afferent neurons have been shown to express HCN2 (Acosta et al, 2012).…”
Section: Expression Of Hcn1-3 In Drg Neurons Of Control Ratsmentioning
confidence: 89%
See 1 more Smart Citation
“…Chaplan et al (2003) also found HCN2 to be expressed by all sizes of DRG neurons in the rat, whereas in the mouse, HCN2 was expressed in about 80% and 60% of large-sized and small-sized DRG neurons, respectively (Moosmang et al, 2001). In the rat trigeminal ganglia, HCN2 has been shown to be expressed by all three neuronal size groups (Wells et al, 2007) or mainly by medium-large-sized neurons (Cho et al, 2009b). At least some of the IB4-negative small neurons that express HCN2 are likely to be lowthreshold mechanoreceptors because this subpopulation of primary afferent neurons have been shown to express HCN2 (Acosta et al, 2012).…”
Section: Expression Of Hcn1-3 In Drg Neurons Of Control Ratsmentioning
confidence: 89%
“…Expression of HCN4 channel subunit was not examined in the present study because its presence in primary sensory neurons is uncertain (Chaplan et al, 2003;Luo et al, 2007;Kouranova et al, 2008) or was found only in about 5% of DRG neurons (Cho et al, 2009b). It should be pointed out that the differences between the various studies in the expression profile of HCN1-HCN4 are likely to be due to the differences in the antibodies and/or species used.…”
Section: Expression Of Hcn1-3 In Drg Neurons Of Control Ratsmentioning
confidence: 95%
“…HCN2 has also been detected in myelinated fibres, including nociceptive Aδ fibres [102][103][104][105]. Finally, the HCN4 isoform appears to be absent or expressed at low levels in sensory neurons [98,105,108]. Finally, the HCN4 isoform appears to be absent or expressed at low levels in sensory neurons [98,105,108].…”
Section: Decreased Neuronal Activitymentioning
confidence: 99%
“…Зміни мембранного потенціалу у відповідь на гіперполяризувальні поштовхи струму: а -нейрони тонічні(1), адаптивні(2) та затриманої генерації(3) по різному відповідали на гіперполяризацію мембрани. Головною особливістю цих відповідей є «вигин» (○), який поступово переходить у стаціонарний стан (•); б -значення коефіцієнтів аномального випрямлення, що залежить від часу при різних рівнях гіперполяризації для 11 тонічних, 7 адаптивних та 3 нейронів затриманої генерації потенціалів дії Характеристика електричної активності нейронів ганглія трійчастого нерва каналів експресуться в нейронах ГТН [18,19]. Наявність або відсутність різних ти-пів цих каналів спричинює відмінності у кінетиці відповідей.…”
Section: результати та їх обговоренняunclassified
“…Наявність або відсутність різних ти-пів цих каналів спричинює відмінності у кінетиці відповідей. Відомо також, що ці канали відіграють важливу роль у генерації імпульсної активності нейронів сенсорних гангліїв [17,18]. Більша частина нейронів генерувала ПД з «горбом» на фазі реполяризації.…”
Section: результати та їх обговоренняunclassified